Indoleamine 2, 3‐dioxygenase 1 promoter hypomethylation is associated with poor prognosis in patients with esophageal cancer. Issue 6 (20th May 2019) - Kiyozumi, Yuki; Baba, Yoshifumi; Okadome, Kazuo; Yagi, Taisuke; Ogata, Yoko; Eto, Kojiro; Hiyoshi, Yukiharu; Ishimoto, Takatsugu; Iwatsuki, Masaaki; Iwagami, Shiro; Miyamoto, Yuji; Yoshida, Naoya; et al.
Abstract: Indoleamine 2, 3‐dioxygenase 1 (IDO1) is a primary enzyme that generates immunosuppressive metabolites. It plays a major role in tumor immunology and is a potential immune‐based therapeutic target. We have reported that IDO1 protein expression was associated with an unfavorable clinical outcome in esophageal cancer. Recently, it has been reported that IDO1 expression is regulated by methylation of the IDO1 promoter. Thus, the aim of this study was to examine the relationship between IDO1 expression, IDO1 promoter methylation, and clinicopathological features in esophageal cancer. We first confirmed changes in IDO1 expression levels in vitro by treating cells with 5‐azacytidine. We then evaluated the relationship between IDO1 expression levels, IDO1 promoter methylation (bisulfite pyrosequencing), and clinicopathological features using 40 frozen samples and 242 formalin‐fixed, paraffin‐embedded samples resected from esophageal cancer patients. We treated cell lines with 5‐azacytidine, and the resulting hypomethylation induced significantly higher IDO1 expression ( P  < .001). In frozen samples, IDO1 expression levels correlated inversely with IDO1 promoter methylation levels ( R  = −0.47, P  = .0019). Furthermore, patients in the IDO1 promoter hypomethylation group (n = 67) had a poor prognosis compared with those in the IDO1 promoter hypermethylation group (n = 175) (overall survival, P  = .011). Our results showed that IDO1 promoter hypomethylation regulated IDO1 expression and was associated with a poor prognosis in esophageal cancer patients. Abstract : Methylation of CpG sites in the indoleamine 2, 3‐dioxygenase 1 (IDO1) promoter regulated IDO1 expression levels. Hypomethylation of IDO1 was associated with poor prognosis in esophageal cancer patients.